Aarupgaard tuegravplads gennem 75 år: Foreløbige betragtninger - Poulsen, Anna Egelund; Rose, Helene Agerskov (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
Aarupgaard urnfield is situated in Southern Jutland, between Gram and Ribe, and visitors can still today catch a glimpse of the largest barrows in the tall grass. The urnfield was discovered in the late 19th century and although minor excavations were carried out over the years, it was excavated almost in its entirety by Erik Jørgensen from Museum Sønderjylland in 1970 – 1972. The excavations revealed c. 1300 well-preserved urnfield graves, making Aarupgaard the largest known urnfield in Denmark. Aarupgaard urnfield has the potential to become a cornerstone in our understanding of Early Iron Age societies, but although many years have passed since its excavation and the material has been included in more projects over the years, the site has never been fully published. A working group was therefore established in 2018, with the aim of preparing Aarupgaard urnfield for publication. Digital registration of the archival material alone is a considerable task, but this is hopefully not the last we hear of Aarupgaard urnfield.